An Efficient Approach on Data Security with Cloud Computing Environment: A Comprehensive Research - Mrs. Anjali Sharma, Dr. Garima Sinha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
this paper discusses the data security in cloud computing. It is a study of data in the cloud and aspects related to it concerning security. As we all know Cloud computing is an emerging domain and security of the data must be protected over the network. Cloud computing is used by many of the organizations for storing the huge amount of data on the clouds. Therefore, there is need to secure the data which may in the form of text, audio, video, etc. There are numerous algorithms designed by the researchers for securing the data on the cloud. The paper will go in to details of data protection methods and approaches used throughout the world to ensure maximum data protection by reducing risks and threats.